LEGAL CONTEXT OF THE LAND RESOURCES PRIVATIOZATION IN UZBEKISTAN - Abdumannabova Muyassarxon Abdurashid qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
INTRODUCTION Land relations occupy a special place in the legal system of any state, and this is particularly true for the Republic of Uzbekistan, where land has historically been treated not as an ordinary object of civil turnover but as “national wealth” subject to direct state control. For more than seven decades under the Soviet system, and for nearly three further decades of post-independence development, land in Uzbekistan remained the exclusive property of the state. The privatization of land resources emerged as one of the most legally and politically sensitive undertakings. Unlike the privatization of industrial enterprises or housing stock, which had already been substantially completed by the late 1990s, the transfer of land into private ownership required not only ordinary legislative amendment but, ultimately, a change to the constitutional order itself. The protection of land resources and their rational use constitute one of the principal directions of state environmental policy. As an integral component of the ecological system, land resources play a vital role in ensuring the stability of the natural environment, as well as in strengthening the material foundation of the state sovereignty and economic potential of the Republic of Uzbekistan.